Articulatory speech measures can be related to the severity of multiple sclerosis - Kieling, Maiara Laís Mallmann; Finkelsztejn, Alessandro; Konzen, Viviana Regina; dos Santos, Vanessa Brzoskowski; Ayres, Annelise; Klein, Iasmin; Rothe-Neves, Rui; Olchik, Maira Rozenfeld (Frontiers in Neurology, 2023)
Background Dysarthria is one of the most frequent communication disorders in patients with Multiple Sclerosis (MS), with an estimated prevalence of around 50%. However, it is unclear if there is a relationship between dysarthria and the severity or duration of the disease. Objective Describe the speech pattern in MS, correlate with clinical data, and compare with controls. Methods A group of MS patients (n = 73) matched to healthy controls (n = 37) by sex and age. Individuals with neurological and/or systemic conditions that could interfere with speech were excluded. MS group clinical data were obtained through the analysis of medical records. The speech assessment consisted of auditory-perceptual and speech acoustic analysis, from recording the following speech tasks: phonation and breathing (sustained vowel/a/); prosody (sentences with different intonation patterns) and articulation (diadochokinesis; spontaneous speech; diphthong/iu/repeatedly). Results In MS, 72.6% of the individuals presented mild dysarthria, with alterations in speech subsystems: phonation, breathing, resonance, and articulation. In the acoustic analysis, individuals with MS were significantly worse than the control group (CG) in the variables: standard deviation of the fundamental frequency (p = 0.001) and maximum phonation time (p = 0.041). In diadochokinesis, individuals with MS had a lower number of syllables, duration, and phonation time, but larger pauses per seconds, and in spontaneous speech, a high number of pauses were evidenced as compared to CG. Correlations were found between phonation time in spontaneous speech and the Expanded Disability Status Scale (EDSS) (r = − 0.238, p = 0.043) and phonation ratio in spontaneous speech and EDSS (r = −0.265, p = 0.023), which indicates a correlation between the number of pauses during spontaneous speech and the severity of the disease. Conclusion The speech profile in MS patients was mild dysarthria, with a decline in the phonatory, respiratory, resonant, and articulatory subsystems of speech, respectively, in order of prevalence. The increased number of pauses during speech and lower rates of phonation ratio can reflect the severity of MS.